Neutralidade da rede no Brasil: uma análise dos contratos de zero rating à luz da legislação brasileira de proteção ao consumidor e à livre concorrência - Brito, Brunna Victória Gurgel de Paiva (Universidade Federal Rural do Semi-Árido, 2019)
This paper will analyze the zero rating contracts traded in Brazil. It will be questioned: do the zero rating contracts pose a threat to the network neutrality adopted by the Civil Internet Framework and, consequently, to the competition and consumer standards? The article was divided into three parts: first, the network neutrality principle, its favorable arguments and its main criticisms, were presented, as well as its prediction in Act no. 12.965/2014 and Decree no. 8.771/2016; then it will be analised the arguments presented in the Administrative Inquiry n. 08700.004314/2016-71, established in the Administrative Council for Economic Defense based on a complaint by the Federal Public Prosecutor about possible network neutrality violation and anti-competitive practices in Brazil; lastly, it will be shown that applications with zero rating contracts dominates Internet users quantitatively. It is concluded that, as currently offered by the operators in the country, the zero rating clauses represent a threat to the entry of new players in the market and violates the basic right of the free will of the consumer.
Artigo Acadêmico
Keywords: Neutralidade de rede; Marco civil da Internet; Zero rating; Direito concorrencial; Direito do consumidor; Network neutrality; Framework for the internet; zero rating; Consumer law; Competition law; Brazilian civil rights; CIENCIAS SOCIAIS APLICADAS::DIREITO